Trilogy and The Five Branding Awareness: Strategies to Build Public Trust in Higher Education - Ach, Rizquha; Abdullah, Abdullah (Journal of Educational Management Research, 2022)
This paper wants to see how far the response of educational institutions to changes in aspects of human life from manual to technological basis. All human activities will become easier to reach. Globalization brings changes in everything, including in the world of education, thus managers of educational institutions are required to always innovate in developing educational institutions, not only producing output equipped with scientific knowledge but also being able to produce graduates who are creative, skilled, and able to compete and can adapt to advances in information technology. Countless educational institutions make competition very tight. To address this, educational institutions need to have an established branding image because the majority of people make decisions in choosing educational institutions by looking at the branding of institutions such as Nurul Jadid University through trilogy and five awareness branding. The results showed that the better the branding owned by the institution, the better the interest and attention of the public to choose the institution.